PROGRAM BRAND AMBASSADOR #SOCIOFELLAS MELALUI AKUN INSTAGRAM @SOCIOLLA - Tiara Jasmine Anindhita; Yustikasari Yustikasari (Sekolah Tinggi Pariwisata Mataram, 2021)
Social media can be used as a medium to communicate and introduce a brand or company. PR & Community PT Social Bella Indonesia utilizes social media as a platform to increase public awareness about the company and the Beauty Journal business line, by making Instagram social media planning and content management in it, as stated in a #Sociofellas program that involves four men as brand ambassadors. The planning process starts with making research and conducting a SWOT analysis. Second, make a program objective, which is specific by considering and making efforts to achieve these goals and objectives. Third, create a program strategy including guidelines, key messages, and recognizing the environment and the target audience to be achieved. Fourth, make tactics, by determining what activities will be posted on social media Instagram @sociolla, and determining what media will be used. Fifth, implementation of the program by making timelines, and budgeting. And the last is evaluation, which is done with social media and digital media monitoring.